Alterações na expressão protéica das células mesangiais em cultura sob os efeitos quimiotóxicos do meio de contraste radiológico iodado, HexabrixR. - Perez, Juliana Dinéia [UNIFESP] (2006)
The kidney is a common target organ for toxic agents, like contrast media (CM). The CM with iodine is normally used in angiography, urography and tomography. CM is filtrated and metabolized in the kidney, being the major cause of acute renal failure (ARF). Nowadays, proteome is actually a powerful tool in the Nephrology Research, mainly in the identification of protein modifications when in contact with toxic agents. This technique also gives the possibility of biomarkers identification to help the physicians in the patient treatments. The aim of this study was to separate by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and to identify by matrix-assisted laser desorption ionization-time-of-flight (MALDI-TOF) mass spectrometry the proteins that were up- or down-regulated in immortalized mesangial cell in culture (IMC) in the presence of CM. We evaluated three groups of IMC: control (CT), manitol (Man) and HexabrixTM (Hx). The samples were treated and submitted to the 2D-PAGE analysis, where the proteins were separated according to their isoelectric points and molecular weights. We identified by MALDI-TOF around 11 proteins. Some proteins were expressed only in the Hx group (Proliferating Cell Nuclear Antigen and Masp 1); others were more expressed in the Man group when compared with Hx and Ct groups (Translationally Controlled Tumor Protein). On the other hand, some proteins were expressed only in the Ct and Man groups (Annexin A3 and DNA ligase), suggesting that probably the Hx caused injury in these cells and it was responsible for the down-regulation of these proteins. Finally, we identified proteins that were expressed in the three cell groups (Heat Shock Protein 27, Heat Shock Protein 84), but with different levels. We concluded that the osmolarity of manitol and Hx could influenciate the alterations in the concentration of a specific protein. We believe that osmolarity and other factors of the CM could be responsible for the nephrotoxicity observed in this model. Proteomic analysis is a promising tool to study the renal pathophysiology making possible in the future the identification of biomarkers of renal diseases that can constitute therapeutically targets, minimizing the actual damages for the ARF.